2011
DOI: 10.4319/lo.2011.56.4.1525
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying rates of methanogenesis and methanotrophy in Lake Kinneret sediments (Israel) using pore‐water profiles

Abstract: Full seasonal sets of chemical and isotope profiles from the pore water of Lake Kinneret (Sea of Galilee, Israel) were produced to study methanogenesis and methanotrophy processes and the couplings between methane (CH 4 ), sulfur, and iron. Sulfate is depleted within the upper 10 cm of the sediment mainly by traditional bacterial sulfate reduction by organic matter. Maximum sulfate reduction rates calculated from sulfate concentration profiles are found at the water-sediment interface (0-1 cm 2 1.4 3 10 212 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 49 publications
3
59
2
Order By: Relevance
“…), but they are still a factor two to three below the flux estimated by the optimized model. Furthermore, the contribution of ebullition to the total fluxes from the sediments during anoxic conditions in the hypolimnion (∼80%) exceeds a previous estimate of 50–75% based on CH 4 budgets within sediment cores (Adler et al ).…”
Section: Discussioncontrasting
confidence: 51%
“…), but they are still a factor two to three below the flux estimated by the optimized model. Furthermore, the contribution of ebullition to the total fluxes from the sediments during anoxic conditions in the hypolimnion (∼80%) exceeds a previous estimate of 50–75% based on CH 4 budgets within sediment cores (Adler et al ).…”
Section: Discussioncontrasting
confidence: 51%
“…One milliliter headspace sample was taken from the crimped vial with a gas‐tight pressure lock after the bottle was shaken vigorously. CH 4 in the headspace was measured on a Focus Gas Chromatograph (Thermo) with ShinCarbon column with precision of 2 μM L −1 (Adler et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Apart from the insights discussed above, the knowledge about free gas within the sediment of LK is rather limited. Adler et al () found bubbles between 7 and 15 cm depth into the sediment at the deepest part of the lake by visual inspection of sediment cores. The decreasing hydrostatic pressure during core recovery can result in the formation of new gas bubbles due to dissolution of CH 4 in the sediment pore water and an expansion of existing bubbles, resulting in a possible bias of this study.…”
Section: Assessmentmentioning
confidence: 99%